KEKERASAN TERHADAP ANAK RESPON PEKERJAAN SOSIAL - Suharto, Edi (Jurnal Kawistara, 2015)
Violence against child become national and global issue. In some developed countries, violence againstchild emotionally, physically, and sexually happens. The same thing also happens in Indonesia soefforts to protect children become a crucial issue, especially for those who are vulnerable. This papershows that boys are more vulnerable than girls. In case of sexual abuse for example, one of the 12 boysare vulnerable to sexual abuse than girls who have a ratio of 1:19. Unfortunately, most children do notknow about social services related to child abuse. Perpetrators of violence are dominated by peoplewho are nearby and familiar with them. For protection of children, its system needs to beresponded tobyrelevantprofessioninsocialwork and it becomeconstitutional mandate